Blood pressure response to dynamic exercise testing in adolescent elite athletes, what is normal? - Wüstenfeld, J. C.; Baersch, F.; Rüdrich, P.; Paech, C.; Wolfarth, B. (Frontiers in Pediatrics, 2022)
Background: In general, only few studies are dedicated to blood pressure behavior under physical stress in children and adolescents. Even less is published about the blood pressure behavior of young high-performance athletes on the ergometer. For this reason, we evaluated the blood pressure behavior under stress compared to non-athletes in a large collective (n = 739) of young high-performance athletes (age 10-20 years, mean 15.8 years, male 442, female 297) of different sports. A complete echocardiographic examination was available in all athletes.